Unir para difundir: o impacto das federativas no crescimento do espiritismo - Betarello, Jeferson (2009)
The present research analyzes the impact on the growth of the formal spiritist contingent, caused by the institutional positioning of its leaderships, which is concretized in the spiritist federative organisms the spiritist federations. It identifies the elements that contribute to the belief, by the federative organisms, especially the Federação Espírita Brasileira (FEB), that the formal spiritist contingent be much superior to that pointed by the Census IBGE/2000. By means of historical surveys on the institutionalization of the Spiritism, it points out ambiguities ever since its origins in France as well as others that came out during the process of consolidation of the Spiritism as a religion in Brazil. In order to identify the impacts, both negative and positive, of the federative organisms on the contingent growth, the theoretical apparatus of the Rational Choice Theory was used, especially the concepts that contribute to the analysis of the success of a religion concerning formal adherence to it. From the analysis of the data obtained from the IBGE censuses, from federative records, and from a research done in the city of Franca-SP, the following conclusions are drawn: the spiritist federative organisms have positively impacted on the contingent growth for their performance in the consolidation of the Spiritism as an important religion in Brazil, by adapting it to the Brazilian context, without leaving the Kardec s fundamentals behind, thus differing it from other mediumnic religions; the spiritist federative organisms have negatively impacted on the contingent growth for sending ambiguous messages to the Spiritist Movement, particularly those related to the science and religion dichotomy, and that affect the actions of the spiritist centers, by transforming them into service renders that encourage attendance but not adherence; for not acknowledging official census data and for not producing data about the contingent, the federative organisms do not subsidize the Spiritist Movement with strategic information that would permit a major presence and a better geographic distribution of the spiritist centers in relation to other religious groups, therefore negatively impacting on the growth of the formal spiritist contingent. However, an exception was noted in Franca-SP, where the spiritist federative organism USE represent a model of positive impact in the growth of the formal spiritist contingent